KONTRIBUSI SEKTOR PERTANIAN DALAM PERTUMBUHAN DAN STABILITAS PRODUK DOMESTIK BRUTO - SYAM, AMIRUDDIN; DERMOREDJO, SAKTYANU K. (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 1, No. 2 Juli 2001)
This research aims to understand the contribution of agriculture sector in Gross Domestic Product (GDP), its stability and its persistency. In GDP, agriculture sector, which is divided, by sub sector compare with other sectors in economics. The results shows: (1) Contribution of agriculture sector in the growth of GDP (1975-1995), the highest share was reached in 1985 (21.05%). If it compare with the contribution of other sectors; (2) In the long term, on interval 14-15, agriculture sector more resistance compared with manufacturing industry sector; however, in the short term agricultural sector is the most persistent. Compare with other sectors. Among agriculture sectors, forestry sub sector is the most persistent in long term compare to other sectors, especially on interval 2-12, follow by food crops sub sector; and (3) Agriculture sector more stable compare with other sectors, except with mining and quarrying. Among agriculture sector, food crops sub sector has higher value in volatility and stability compare with other sectors.
Keywords: Agriculture Sector, Contribution, and Stability, Gross Domestic Product.